Measure-Valued Markov Processes and Stochastic Flows - Dorogovtsev, A. A. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We consider a new class of Markov processes in the space of measures with constant mass. We present the construction of such processes in terms of probabilities that control the motion of individual particles. We study additive functionals of such processes and give examples related to stochastic flows with interaction.